A randomized controlled study for the treatment of middle-aged and old-aged lumbar disc herniation by Shis spine balance manipulation combined with bone and muscle guidance. Issue 51 (18th December 2020) - Xu, Jinhai; Ding, Xing; Wu, Jinze; Zhou, Xiaoning; Jin, Kun; Yan, Ming; Ma, Junming; Wu, Xuequn; Ye, Jie; Mo, Wen
Abstract : Abstract: Ninety percent of elderly patients with lumbar disc herniation (LDH) have problems with the mechanics of the spine and muscle tissue. Shi-style spine balance manipulation combined with guidance (Daoyin) of muscle and bone as an alternative therapy for LDH can tone the muscle groups around the spine and maintain optimal mechanical and static sagittal balance of the spine. This study will be performed to investigate the effect of a combination of Shi-style spine balance manipulation and Daoyin therapy on LDH in middle-aged and elderly patients. In this non-blinded, randomized controlled trial, 72 eligible patients will be randomly divided into a treatment group (Shi-style spine balance manipulation combined with Daoyin therapy) and a control group (lumbar mechanical traction). Before and after the intervention, lumbar X-ray and magnetic resonance imaging examinations will be performed to observe the sagittal balance parameters of the spine and pelvis and the lumbar muscle strength. The visual analog scale score, Oswestry disability index score, and pressure pain threshold will be evaluated at baseline and at 2, 4, 12, and 24 weeks. During the treatment period, any signs of acute adverse events, such as paralysis of the lower extremities or cauda equina syndrome, will be recorded at each visit. Although Shi-style spine manipulation combined with Daoyin therapy has been used in the treatment of LDH in middle-aged and elderly people in China for many years, there is no consensus on its effectiveness. This experiment will provide convincing evidence of the efficacy of Shi-style spine manipulation combined with Daoyin therapy in the treatment of LDH in middle-aged and elderly people.